Pengaruh Pemberian Sari Kacang Hijau Terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil Anemia - Satria, Epi; Faisal, Afrah Diba (Poltekkes Kemenkes Padang, 2023)
Anemia is a condition where the number and size of red blood cells or hemoglobin concentration is below the normal limit value. It is estimated that 52.5% of women in Southeast Asia experience anemia. Iron content. Green beans are a source of vegetable protein, vitamins (A, B1, C and E), as well as several other substances that are very beneficial for the human body. The aim of this research was to see the effect of giving green bean juice on increasing hemoglobin levels of anemic pregnant women in the Lubuk Buaya Padang Health Center work area. The research design used quantitative quasi-experimental methods, one group pretest-posttest design. The sample size was 15 pregnant women. Research results The average hemoglobin levels of pregnant women before and after being given green bean juice in the treatment group were 10.5 gr/dL and 11.4 gr/dl. In these results there was an increase in hemoglobin levels. There is an effect of giving green bean juice on increasing hemoglobin levels in pregnant women with anemia, the result is p value = 0.000 and the significance value is greater than 5% (p=0.000<0.05 for the variable Hb level (0.000). This means that giving green bean juice can increase Hb levels of pregnant women. This study concluded that there was an effect of giving green bean juice on increasing the value of hemoglobin levels in pregnant women.